Reinterpretasi Kontroversi Kepemimpinan non-Muslim dalam Alquran - Rodin, Dede (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2017)
This article aimed to explore several kinds of understanding and interpretation towards the Qur’anic idea on non-Muslim leadership. Some Muslim scholars’ respond would be a case of study to see their logical reason and their interpretation of the Qur’an on the issue of non-Muslim leadership. The study obtained the following conclusions: first, there are some gaps or perhaps a shifting paradigm between the classical idea of non-Muslim with the modern scholars. Those who lived in the modern times, to some extent, are holding an inclusive idea to allow non-Muslim be a leader in Muslim society. This is because they see that the command of the Qur’an to forbid non-Muslim to hold a leadership is limited to whom they are hostile to Islam and Muslims. Hence the act of banning should not be apllied in general. On the other hand, the historical context of the verse (sabab al-nuzûl) also suggests that the nuance of confrontation between Muslims and non-Muslims is part of the consisting code of conduct at that time, so that the verses above should be put into consideration if the conditions are in peace.